Pengaruh Pertumbuhan Aktiva Produktif, Dana Pihak Ketiga, Dan Ukuran Perusahaan Terhadap Profitabilitas Lembaga Perkreditan Desa Di kabupaten Badung - Prapita Cahyani, Ni Putu Dian; Dana, I Made (E-Jurnal Manajemen, 2014)
Lembaga Prekreditan Desa is one element that runs Pakraman institutional financial potential with the aim to encourage rural economic development manners . The ability to generate profits is called profitability , to gain a high profit to consider the factors that affect profitability . The purpose of this study was to determine the effect of growth in earning assets , deposits , and company size on profitability LPD in Badung . The results of simultaneous testing ( F-test ) showed that credit growth , deposit growth , deposit growth and the size of the company and a significant positive effect on the profitability of LPD in Badung . Partial test ( t-test ) showed that the credit variable positive and significant effect on profitability , while growth in savings deposits and no significant negative effect on profitability . Partially firm size and significant negative effect on profitability LPD in Badung . Keywords : credit growth , deposit growth , deposit growth , firm size , profitability , LPD